Low temperature synthesis of magnetite and maghemite nanoparticles - Bhagwat, Shrikant; Singh, Hema; Athawale, Anjali; Hannoyer, Beatrice; Jouen, Samuel; Lefez, Benoit; Kundaliya, Darshan; Pasricha, Renu; Kulkarni, Shailaja; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2007)
We report on the synthesis of iron oxide nanoparticles below 100 degrees C by a simple chemical protocol. The uniqueness of the method lies in the use of Ferrous ammoniurn sulphate (in conjugation with FeCl3) which helps maintain the stability of Fe-2+ state in the reaction sequence thereby controlling the phase formation. Hexamine was added as the stabilizer. The nanoparticles synthesized at three different temperatures viz, 5 degrees, 27 degrees, and 95 degrees C are characterized by several techniques. Generally, when a mixture of Fe3+ and Fe2+ is added to sodium hydroxide, alpha-Fe2O3 (the anti-ferromagnetic phase) is formed after the dehydration process of the hydroxide. In our case however, the phases formed at all the three temperatures were found to be ferro (ferri) magnetic, implying modification of the formation chemistry due to the specifics of our method. The nanoparticles synthesized at the lowest temperature exhibit magnetite phase, while increase in growth temperature to 95 degrees C leads to the maghemite phase.
Keywords: low temperature synthesis; maghemite; magnetite; Nanoparticles

Bacteria-mediated precursor-dependent biosynthesis of superparamagnetic iron oxide and iron sulfide nanoparticles - Bharde, Atul A.; Parikh, Rasesh Y.; Baidakova, Marina; Jouen, Samuel; Hannoyer, Beatrice; Enoki, Toshiaki; Bhagavatula L. V. Prasad; Shouche, Yogesh S.; Ogale, Satishchandra B.; Sastry, Murali (Langmuir, 2008)
The bacterium Actinobacter sp. has been shown to be capable of extracellularly synthesizing iron based magnetic nanoparticles, namely maghemite (gamma-Fe2O3) and greigite (Fe3S4) Under ambient conditions depending on the nature of precursors used. More precisely, the bacterium synthesized maghemite when reacted with ferric chloride and iron sulfide when exposed to the aqueous solution of ferric chloride-ferrous sulfate. Challenging the bacterium with different metal ions resulted in induction of different proteins, which bring about the specific biochemical transformations in each case leading to the observed products. Maghemite and iron sulfide nanoparticles show superparamagnetic characteristics as expected. Compared to the earlier reports of magnetite and greigite synthesis by magnetotactic bacteria and iron reducing bacteria, which take place strictly under anaerobic conditions, the present procedure offers significant advancement since the reaction occurs under aerobic condition. Moreover, reaction end products can be tuned by the choice of precursors used.

Non-templated hydrothermal growth of anisotropic magnetite nanostructures using hexamine as the directing agent - Bhagwat, S. V.; Jouen, Samuel; Kundaliya, D. C.; Singh, H.; Jagadale, Tushar C.; Athawale, A. A.; Lofland, S. E.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2009)
Anisotropic growth of magnetite (Fe(3)O(4)) nanoparticles is achieved in a hydrothermal growth process using hexamine to play a dual role of oxide forming and directing agent. The samples are characterized by X-ray diffraction, scanning electron microscopy, high resolution transmission electron microscopy, squid magnetometry, ferromagnetic resonance technique, diffuse reflectance spectroscopy and Mossbauer spectroscopy, which collectively establish the formation of Fe(3)O(4) phase. Anisotropic structures such as nanorods and nanotubules are revealed and these are shown to exhibit good humidity sensing properties.
Keywords: Anisotropic Nanostructures; Hexamine; hydrothermal; magnetite; Mossbauer

Elucidation of the role of hexamine and other precursors in the formation of magnetite nanorods and their stoichiometry - Singh, Hema; Bhagwat, Shrikant; Jouen, Samuel; Lefez, Benoit; Athawale, Anjali A.; Hannoyer, Beatrice; Ogale, Satishchandra (Physical Chemistry Chemical Physics, 2010)
Hexamine is known to assist anisotropic growth of metal oxides and the same is also found to be true for magnetite nanosynthesis. In this work we elucidate the role of hexamine and other precursors in the formation of magnetite nanorods by the hydrothermal route and their stoichiometry. Various others hydrolyzing agents such as sodium hydroxide (NaOH), sodium hydroxide + hexamine, ammonia (NH(3)), ammonia + formaldehyde are also studied. The synthesized nanoparticles are characterized with the help of various techniques such as X-ray diffraction (XRD), FT-IR spectroscopy, UV-VIS-NIR spectroscopy, transmission electron microscopy (TEM), Mossbauer spectroscopy and SQUID magnetization measurements. It is found that only when ferric chloride, ferrous ammonium sulfate (FAS) and hexamine are used, well defined nanorods are formed. When sodium hydroxide and hexamine are used as a hydrolyzing system nearly spherical nanoparticles with small size (similar to 13 nm) are formed, as compared to the case of sodium hydroxide alone which leads to bigger cube like nanoparticles. Interestingly the decomposition products of hexamine do not lead to nanorod formation. Thus, slow decomposition of hexamine at elevated temperature and the consequent slow rise in pH is the key to the anisotropic growth of the iron oxide system.

Room temperature synthesis of rutile TiO2 hierarchical nanoneedle flower morphology for dye sensitized solar cell - Hyam, Rajeshkumar S.; Bhosale, Reshma K.; Lee, Wonjoo; Han, Sung-Hwan; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Nanoscience and Nanotechnology, 2010)
Rutile TiO2 nanoneedle flowers (representing concurrent nano-micro hierarchical morphology) with high shape anisotropy ratio are synthesized at room temperature by using a simple and efficient one step electrochemical process of anodic dissolution. This process employs highly acidic bath of perchloric acid (pH < 2) and a large current density on the surface of Titanium foil to form nanostructures. The diameter and length of rutile TiO2 nanoneedle is similar to 8 nm and 100 nm respectively (aspect ratio > 10). Dye sensitized solar cell (DSSC) configured using such rutile TiO2 flowers is shown to exhibit IPCE of 30% and power conversion efficiency of similar to 3.6%.
Keywords: Anodization; DSSC; Nanoneedles; Rutile TiO2

Enhanced DSSC performance with high surface area thin anatase TiO2 nanoleaves - Dhas, Vivek V.; Muduli, Subas; Agarkar, Shruti A.; Rana, Abhimanyu; Hannoyer, Beatrice; Banerjee, Rahul; Ogale, Satishchandra B. (Solar Energy, 2011)
Thin anatase TiO2 nanoleaves (NLs) with high surface area (similar to 93 m(2)/g) are synthesized by hydrothermal route and dye-sensitized solar cells (DSSC) made using such NLs are compared with those made with hydro-thermally synthesized TiO2 nanoparticles and the Degussa P25 powder. The NLs-based DSSCs show increment of 16% and 24% in the total conversion efficiency over the cells made with NPs and P25 respectively. Interestingly, the highest increment in the conversion efficiency (similar to 35%) is achieved for cells made using a 50:50 (wt/wt) mixture of NLs and NPs. In this case the dye loading is found to be >50% higher than the case of NP films. Moreover the DC resistance of diffusion of I-3(-) in electrolyte (as revealed by the electrochemical impedance spectroscopy) is substantially lower than the NP film case, other cell parameters being nominally comparable. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Dye-sensitized solar cells; Electrochemical impedance spectroscopy; hydrothermal

Evidence of lateral heat transfer during laser assisted atom probe tomography analysis of large band gap materials - Bachhav, Mukesh N.; Danoix, R.; Vurpillot, F.; Hannoyer, Beatrice; Ogale, Satishchandra B.; Danoix, F. (Applied Physics Letters, 2011)
Investigation of wustite (FeO), iron (Fe), and silicon (Si) specimens by infrared laser assisted three dimensional atom probe tomography shows evidence of confined surface absorption of the laser energy as the mechanism of laser assisted field evaporation for high band gap materials. The absorption region is shown to be located on the laser illumination side, close to the specimen apex. A simple model based on thermal diffusivity and spatial extent of the absorption region is derived and applied to the experimental results. The values of thermal diffusivity thus obtained are in good agreement with the published data. (C) 2011 American Institute of Physics. [doi:10.1063/1.3622647]

From graphite oxide to highly water dispersible functionalized graphene by single step plant extract-induced deoxygenation - Mhamane, Dattakumar; Ramadan, Wegdan; Fawzy, Manal; Rana, Abhimanyu; Dubey, Megha; Rode, Chandrashekhar; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra (Green Chemistry, 2011)
We report a single step facile synthesis of highly water dispersible functionalized graphene nanosheets by plant extract-induced deoxygenation of graphite oxide (GO). The results of various characterizations reveal that the properties of such plant extract-converted graphene nanosheets (PCGN) are comparable to chemically converted graphene nanosheets (CCG). These results open a green route to the emerging graphene-based technologies.

Investigation of wustite (Fe1-xO) by femtosecond laser assisted atom probe tomography - Bachhav, Mukesh N.; Danoix, R.; Danoix, F.; Hannoyer, Beatrice; Ogale, Satishchandra B.; Vurpillot, F. (Ultramicroscopy, 2011)
In this paper, we report results obtained from laser assisted three-dimensional (3-D) atom probe tomography (APT) on wustite (Fe1-xO). Oxides are generally insulating and hence hard to analyse in conventional electrical assisted APT. To overcome this problem, femtosecond laser pulses are used instead of voltage pulses. Here we discuss some aspects of pulsed laser field evaporation and optimization of parameters to achieve better chemical accuracy. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Atom probe tomography; Laser assisted field evaporation; Wustite

Maghemite (hematite) core (shell) nanorods via thermolysis of a molecular solid of Fe-complex - Chaudhari, N. S.; Warule, S. S.; Muduli, Subas; Kale, B. B.; Jouen, Samuel; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Dalton Transactions, 2011)
An Fe-metal complex with 2'-hydroxy chalcone (2'-HC) ligands [Fe(III) (2'-hydroxy chalcone) 3] is synthesized by a chemical route and is subjected to different thermal treatments. Upon thermolysis in air at 450 degrees C for 3 h the complex yields maghemite (gamma-Fe(2)O(3)) nanorods with a thin hematite (alpha-Fe(2)O(3)) shell. X-Ray diffraction (XRD), Mossbauer spectroscopy, diffuse reflectance spectroscopy (UV-DRS), high resolution transmission electron microscopy (HR-TEM), field emission scanning electron microscopy (FE-SEM) and vibrating sample magnetometry (VSM) are used to characterize the samples. The stability of the ligand and the Fe-complex is further examined by using thermogravimmetric/differential thermal analysis (TGA/DTA). We suggest a residual ligand controlled mechanism for the formation of an anisotropic nanostructure in a crumbling molecular solid undergoing ligand decomposition. Since the band gap of iron oxide is in the visible range, we explored the use of our core shell nano-rod sample for photocatalytic activity for H(2) generation by H(2)S splitting under solar light. We observed high photocatalytic activity for hydrogen generation (75 ml h(-1)).

Magnetite/CdTe magnetic-fluorescent composite nanosystem for magnetic separation and bio-imaging - Kale, Anup; Kale, Sonia; Yadav, Prasad; Gholap, Haribhau; Pasricha, Renu; Jog, Jyoti Prakash; Lefez, Benoit; Hannoyer, Beatrice; Shastry, Padma; Ogale, Satishchandra B. (Nanotechnology, 2011)
A new synthesis protocol is described to obtain a CdTe decorated magnetite bifunctional nanosystem via dodecylamine (DDA) as cross linker. High resolution transmission electron microscopy (HRTEM), energy-dispersive x-ray spectroscopy (EDAX), vibrating sample magnetometry (VSM), Fourier transform infrared spectroscopy (FTIR), diffuse reflectance spectroscopy (DRS) and fluorescence microscopy are used to characterize the constitution, size, composition and physical properties of these superparamagnetic-fluorescent nanoparticles. These CdTe decorated magnetite nanoparticles were then functionalized with anti-epidermal growth factor receptor (EGFR) antibody to specifically target cells expressing this receptor. The EGFR is a transmembrane glycoprotein and is expressed on tumor cells from different tissue origins including human leukemic cell line Molt-4 cells. The magnetite-CdTe composite nanosystem is shown to perform excellently for specific selection, magnetic separation and fluorescent detection of EGFR positive Molt-4 cells from a mixed population. Flow cytometry and confocal laser scanning microscopy results show that this composite nanosystem has great potential in antibody functionalized magnetic separation and imaging of cells using cell surface receptor antibody.

From small aromatic molecules to functional nanostructured carbon by pulsed laser-induced photochemical stitching - Gokhale, R. R.; Thakare, V. P.; Warule, S.; Lefez, Benoit; Hannoyer, Beatrice; Jog, Jyoti Prakash; Ogale, S. B. (AIP Advances, 2012)
A novel route employing UV laser pulses (KrF Excimer, 248 nm) to cleave small aromatic molecules and stitch the generated free radicals into functional nanostructured forms of carbon is introduced. The process differs distinctly from any strategies wherein the aromatic rings are broken in the primary process. It is demonstrated that this pulsed laser-induced photochemical stitching (PLPS) process when applied to routine laboratory solvents (or toxic chemical wastes when discarded) Chlorobenzene and o-Dichlorobenzene yields Carbon Nanospheres (CNSs) comprising of graphene-like sheets assembled in onion-like configurations. This room temperature process implemented under normal laboratory conditions is versatile and clearly applicable to the whole family of haloaromatic compounds without and with additions of precursors or other nanomaterials. We further bring out its applicability for synthesis of metal-oxide based carbon nanocomposites. Copyright 2012 Author(s). This article is distributed under a Creative Commons Attribution 3.0 Unported License. [http://dx.doi.org/10.1063/1.4721268]

Laser synthesized super-hydrophobic conducting carbon with broccoli-type morphology as a counter-electrode for dye sensitized solar cells - Gokhale, Rohan; Agarkar, Shruti A.; Debgupta, Joyashish; Shinde, Deodatta; Lefez, Benoit; Banerjee, Abhik; Jog, Jyoti Prakash; More, Mahendra A.; Hannoyer, Beatrice; Ogale, Satishchandra B. (Nanoscale, 2012)
A laser photochemical process is introduced to realize superhydrophobic conducting carbon coatings with broccoli-type hierarchical morphology for use as a metal-free counter electrode in a dye sensitized solar cell. The process involves pulsed excimer laser irradiation of a thin layer of liquid haloaromatic organic solvent o-dichlorobenzene (DCB). The coating reflects a carbon nanoparticle-self assembled and process-controlled morphology that yields solar to electric power conversion efficiency of 5.1% as opposed to 6.2% obtained with the conventional Pt-based electrode.

MOF derived porous carbon-Fe3O4 nanocomposite as a high performance, recyclable environmental superadsorbent - Banerjee, Abhik; Gokhale, Rohan; Bhatnagar, Sumit; Jog, Jyoti Prakash; Bhardwaj, Monika; Lefez, Benoit; Hannoyer, Beatrice; Ogale, Satishchandra B. (Journal of Materials Chemistry, 2012)
A high surface area carbon composite with Fe3O4 nanoparticles is synthesized by pyrolysis of an iron containing Metal Organic Framework (MOF). The composite can be prepared by annealing the MOF at different temperatures (500 degrees C and 600 degrees C), each case exhibiting unique properties in terms of the hydrophobic behaviour and surface area, resulting in specific applicability domains. We highlight the exceptional behaviour of this material as a magnetically separable and recyclable superadsorbent for removal and recovery of environmental pollutants (oil/hydrocarbon and dye/phenol).

Hollow nanogold/meso-magnetite composite: pulsed laser synthesis, properties, and biosensing application - Chaudhari, Nilima; Warule, Sambhaji; Agrawal, Shailaja; Thakare, Vishal; Jouen, Samuel; Hannoyer, Beatrice; Kale, Bharat; Paknikar, Kishore; Ogale, Satishchandra B. (Journal of Nanoparticle Research, 2013)
A facile and template-free UV (Excimer) laser photolysis process is demonstrated to transform a Fe-complex into unique hollow Fe3O4 nanosphere morphology with each sphere having nanometric pores and an opening. Depending on the Fe-complex concentration and processing time interesting configurations are seen to evolve. When an identical process is applied to a mixture of Fe-complex and chloroauric acid an enthrallingly decorated Au-Fe3O4 nanostructure evolves, with Au nanoparticles surface-loaded on mesospheric Fe3O4. This room temperature process implemented under normal laboratory conditions is clearly versatile and applicable to heterojunction nanomaterials synthesis in a single-step process. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml. The test results demonstrate linear sensing response in the range of 10(3)-10(5) cfu/ml. We also show that these nanostructures can be used for simple electrical conductivity-based biosensing since they show dramatic conductivity change in a simple drop-cast test. A new laser-based approach to the synthesis of unique hollow sphere morphology of magnetite (Fe3O4) without and with Au nanoparticle decoration is presented. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml.
Keywords: E. coli cells; Fe-complex; Meso-magnetite; Nanobiotechnology; Nanocomposite; Pulse laser irradiation